2009
DOI: 10.1088/0004-637x/692/2/1447
|View full text |Cite
|
Sign up to set email alerts
|

Λcdm Satellites and H I Companions—the Arecibo Alfa Survey of NGC 2903

Abstract: We have conducted a deep, complete H i survey, using Arecibo/Arecibo L-band Feed Array (ALFA), of a field centered on the nearby, isolated galaxy, NGC 2903, which is similar to the Milky Way in its properties. The field size was 150 kpc × 260 kpc and the final velocity range spanned from 100 to 1133 km s −1 . The ALFA beams have been mapped as a function of azimuth and cleaned from each azimuth-specific cube prior to forming final cubes. The final H i data are sensitive down to an H i mass of 2 × 10 5 M and co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 94 publications
(130 reference statements)
2
46
0
Order By: Relevance
“…A total of ∼30 000 galaxies are expected to be detected. The first galaxy catalogs are Giovanelli et al (2007), Saintonge et al (2008), Kent et al (2008), Martin et al (2009), Stierwalt et al (2009), the subsequent α.40 catalog (Haynes et al 2011) Cortese et al (2008), Irwin et al (2009), Minchin et al (2010, Davies et al (2011), Taylor et al (2012, 2014a, Minchin et al (2016), Keenan et al (2016); 4. GASS: pointed survey at the Arecibo 305 m telescope (Catinella et al 2012) of 666 galaxies with stellar masses greater than 10 10 M selected from the SDSS spectroscopic and the Galaxy Evolution Explorer (GALEX) ultraviolet imaging surveys.…”
Section: Introductionmentioning
confidence: 99%
“…A total of ∼30 000 galaxies are expected to be detected. The first galaxy catalogs are Giovanelli et al (2007), Saintonge et al (2008), Kent et al (2008), Martin et al (2009), Stierwalt et al (2009), the subsequent α.40 catalog (Haynes et al 2011) Cortese et al (2008), Irwin et al (2009), Minchin et al (2010, Davies et al (2011), Taylor et al (2012, 2014a, Minchin et al (2016), Keenan et al (2016); 4. GASS: pointed survey at the Arecibo 305 m telescope (Catinella et al 2012) of 666 galaxies with stellar masses greater than 10 10 M selected from the SDSS spectroscopic and the Galaxy Evolution Explorer (GALEX) ultraviolet imaging surveys.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work (Irwin et al 2009) on the H i content of NGC 2903 has shown that it possesses a large H i envelope of around three times its optical size. They also found a small H i companion 64 kpc away from the galaxy in projection, which adds to a previously known small stellar companion.…”
Section: Introductionmentioning
confidence: 99%
“…These anomalous H I clouds appear to be the analogs of the large HVC complexes in the MW with substantial H I masses, large extents of several kpcs and projected separations from the galactic disks of ∼ 10 − 20 kpc. Other dedicated surveys of other nearby galaxies and galaxy groups reveal no HVC analogs down to ∼ 4 × 10 5 M at larger distances from galaxies (Pisano et al 2007;Irwin et al 2009). …”
Section: Pos(aaska14)129mentioning
confidence: 87%